Virulence factors in carbapenem-resistant hypervirulent Klebsiella pneumoniae - Mendes, Gabriel; Santos, Maria Leonor; Ramalho, João F.; Duarte, Aida; Caneiras, Cátia (Frontiers in Microbiology, 2023)
Hypervirulence and carbapenem-resistant have emerged as two distinct evolutionary pathotypes of Klebsiella pneumoniae, with both reaching their epidemic success and posing a great threat to public health. However, as the boundaries separating these two pathotypes fade, we assist a worrisome convergence in certain high-risk clones, causing hospital outbreaks and challenging every therapeutic option available. To better understand the basic biology of these pathogens, this review aimed to describe the virulence factors and their distribution worldwide among carbapenem-resistant highly virulent or hypervirulent K. pneumoniae strains, as well as to understand the interplay of these virulence strains with the carbapenemase produced and the sequence type of such strains. As we witness a shift in healthcare settings where carbapenem-resistant highly virulent or hypervirulent K. pneumoniae are beginning to emerge and replace classical K. pneumoniae strains, a better understanding of these strains is urgently needed for immediate and appropriate response.